Association of Osteoporosis with Antibiotic Resistance among Postmenopausal Women with Open Tibial Fractures: Osteoporosis and Antibiotics in Postmenopausal Women - Bhatti, Rasheed Ahmed; Maheshwari, Lachman Das; Ahmed, Adnan; Jhokio, Muhammad Faraz; Lakho, Arshad Sattar; Abro, Akbar Gohar (Pakistan Journal of Health Sciences, 2024)
Osteoporosis is common among postmenopausal women and can complicate the healing of open tibial fractures. Antibiotic resistance is a growing concern in treatment. Yet, the connection between osteoporosis and antibiotic resistance remains unclear, needing the investigation for improved patient care. Objective: To explore the association between osteoporosis and antibiotic resistance among postmenopausal female patients with open tibial fractures. Methods: This cross-sectional study was conducted at Department of Orthopedic Surgery, Liaquat University of Medical and Health Sciences, Jamshoro, with sample size of 240 postmenopausal women with open tibial fractures and signs of infection within one week of the fracture. Participants were chosen via non-probability sampling method. Bacteriological samples for culture were obtained from secretions adjacent to the infected tissue. Data analysis was conducted using SPSS version 21.0. Results: The majority of osteoporotic patients experienced Road Traffic Accidents (RTA) (42.5%), followed by falls from height (35.3%), while firearm injuries were less common (22.2%). Staphylococcus aureus was the most common pathogen in both osteoporotic (40%) and non-osteoporotic (39.9%) patients, followed by Escherichia coli, Methicillin-Resistant Staphylococcus Aureus (MRSA), Klebsiella, and Pseudomonas aeruginosa. Antibiotic resistance was predominantly found against S. aureus, MRSA, Klebsiella and E. coli. Co-Trimoxazole exhibited the highest resistance rates across all four bacterial organisms, ranging from 34% to 50%. Conclusions: The study found varying antibiotic resistance patterns across various pathogens, with notable resistance observed MRSA strains. Antibiotic resistance was observed in osteoporotic group, with Co-Trimoxazole showing the highest resistance rates.